Intestinal mucinous adenocarcinoma with metastases to epididymis, testis and tunica albuginea in a dog - Wasques, Danilo G.; Fernandes, Natália C. C. A.; Ressio, Rodrigo A.; Guerra, Juliana M. (Brazilian Journal of Veterinary Pathology, 2017)
A case of intestinal mucinous adenocarcinoma with metastasis to gonadal tissue is reported. A 13-year-old, male, poodle dog presented with intestinal and peritoneal masses, as well as infiltrative masses in testicular tunics. Samples were biopsied and submitted for histopathological analysis. Microscopically, intestinal lesion consisted of an adenocarcinoma (mucinous type), with infiltration of muscular layers and mesenteric adipose tissue. In gonadal tissue, there was neoplastic infiltration of epididymis and tunica albuginea (with a predominantly tubular pattern), and testicular parenchyma (with a predominantly signet-ring cell pattern). Immunohistochemistry was positive for CDX2 and pancytokeratin, and negative for vimentin, supporting the diagnosis of intestinal mucinous adenocarcinoma with metastases to epididymis, testis and tunica albuginea.